Serendipitous, cross familial discovery of the first long-range chemical attractants for antlions (Neuroptera: Myrmeleontidae): (1R,2S,5R,8R)-iridodial and Z,E-nepetalactol - Zhang, Qing-He; Zhou, Guiji; Hoover, Doreen R.; Michaelson, Neil J.; Bryant, Paul; Margaryan, Armenak; Chauhan, Kamlesh R.; Aldrich, Jeffrey R.; Schneidmiller, Rodney G. (Frontiers in Ecology and Evolution, 2015)
Synthetic (1R,2S,5R,8R)-iridodial, the key pheromone component of many green lacewings in the genus Chrysopa, strongly attracted adult males and females of the North American antlion, Dendroleon speciosus Banks. In addition, one of the common sex pheromone components of many aphids to which Chrysopa spp. are weakly attracted, Z,E-nepetalactol, was also weakly attractive to D. speciosus adults. Iridodial and Z,E-nepetalactol also elicited strong and weak electroantennogram detector (EAD) responses, respectively, in D. speciosus adults. Previously reported semiochemicals from European and Israeli antlion species did not elicit EAD or behavioral responses from D. speciosus adults. The earlier studied antlions release volatile chemicals from male-specific metathoracic glands associated with structures on the hind wings (Eltringham’s organs) that are thought to enhance evaporation of the secretion. Although D. speciosus males have Eltringham’s organs similar to those of other antlion species, we discovered that D. speciosus males have a pair of white tubular glands that extend posteriorly into the abdomen, opening in the resting pits of the Eltringham’s organs. Further gas chromatograph (GC)-EAD analysis of another commercially available antlion species, Myrmeleon crudelis Walker, showed that this species did not respond to the lacewing or aphid related volatile compounds, but strongly responded to the reported antlion semiochemicals, namely, nerol, 10-homonerol and nerol oxide. The male-specific abdominal glands of D. speciosus are presumably pheromone glands; hopefully, positive verification of this supposition will help clarify the semiochemical relationships between antlions, lacewings and aphids.